Managerial Openness to Change and the Introduction of GDSS: Explaining Initial Success and Failure in Decision Conferencing - McCartt, Anne T.; Rohrbaugh, John (Organization Science, 1995)
The term Group Decision Support System (GDSS) refers broadly to any application of information technology that supports the work of groups. As more organizations increasingly explore possible applications of GDSS in ways that have the potential to alter managerial routines, the extent of managerial openness to change will be tested at least as much as the new technology. The relation of managerial openness to the successful introduction of GDSS was studied by analyzing a survey of participants in 26 decision conferences hosted by the Decision Techtronics Group of the State University of New York. The perceived benefit of each conference was assessed by a global outcome scale. Eight additional scales were employed to measure group decision process effectiveness, based on the Competing Values Approach to organizational analysis. Results indicated that conferences were evaluated as most beneficial by flexible client organizations that appeared open to the initial use of GDSS. As expected, positive outcomes also were found to be associated with conferences that involved fewer participants and in which participants believed that important decisions had been made. To the extent that the process of GDSS introduction can be managed to avoid failures, the research findings strongly encourage the design of meetings that both efficiently focus on the task (i.e., are highly goal centered) while simultaneously engaging the full involvement of every group member (i.e., are highly participatory). While new technology must be repeatedly modified following adoption to suit the unique demands of each workplace, an organizational unit also must be able to change appropriately its established structures and processes to make accommodation. Such mutual adaptation suggests that the eventual assimilation of new technology will become threatened wherever it is rigidly introduced or wherever management teams are not flexible enough to alter their decision-making routines at the time of initiation.